A New X-Ray Tidal Disruption Event Candidate with Fast Variability. (1st May 2022) - Hampel, J.; Komossa, S.; Greiner, J.; Reiprich, T. H.; Freyberg, M.; Erben, T.
Abstract: During a close encounter between a star and a supermassive black hole, the star can get disrupted by the black hole's tidal forces, resulting in a tidal disruption event (TDE). The accretion of the star's material onto the black hole produces strong emission in different wavelength regimes. Here we report the discovery with the Roentgen Satellite (ROSAT) of an X-ray-selected transient source in an optically non-active galaxy. At the location R.A.: 13 h 31 m 57.ˢ66 and decl.: −32°43′19.″7 a sudden rise in X-ray luminosity by a factor of 8 within 8 days has been observed. Additionally, a very soft X-ray spectrum with a blackbody temperature kT = 0.1 keV and a peak luminosity of at least 1 × 10 43 erg s −1 suggests a TDE interpretation, and the observed properties are very similar to previously identified soft X-ray (ROSAT) TDEs. An optical spectrum taken of the galaxy at the position of RXJ133157.6324319.7 six years after the X-ray outburst does not show any emission lines as would be expected from a persistent active galactic nucleus. The redshift of the galaxy is determined to be 0.051 based on absorption lines. It is therefore likely a member of the galaxy cluster A3560. The rise in X-ray luminosity happens within 8 days and thus appears to be fast for such an event. No X-ray emission was detected 170 days before and 165 days after the event, and none was detected 25 yr later with the Neil Gehrels Swift Observatory. The change in X-ray luminosity is at least a factor of 40.